Effect of High Temperature (600°C) on Mechanical Properties, Mineral Composition, and Microfracture Characteristics of Sandstone - Jian Li; Zhao-Wen Du; Zhong-Ping Guo (Advances in Materials Science and Engineering)
Rock destruction under high-temperature conditions is a key issue for nuclear waste treatment projects, underground coal gasification, and improvement of the use of geothermal energy for heating. Therefore, in this study, various methods and techniques were integrated to study the changes in mechanical properties, mineral composition, and microscopic fracture characteristics of Sichuan sandstone treated at 600°C. First, the fracture toughness and indirect tensile strength of untreated sandstones and high-temperature treated sandstones were tested by the MTS testing machine, and the double-K model (DKFM) was used to estimate the unstable fracture toughness. Then, the diffraction spectra of sandstone were analyzed with an X-ray diffractometer to determine the mineral composition change after heat treatment. Finally, the microscopic features of sandstone were observed through a scanning electron microscope (SEM) and optical microscope. The results show the following. (1) There is no significant change in the tensile strength and fracture toughness of Sichuan sandstone treated at 600°C. (2) The brittleness of Sichuan sandstone decreases and the ductility increases after high-temperature treatment. (3) The unstable fracture toughness value Kun obtained by the double-K model (DKFM) is significantly larger than the apparent fracture toughness value Kif. (4) After treatment at 600°C, the clay minerals in the sandstone changed significantly. Kaolinite is dehydroxylated to metakaolinite, which may increase the ductility of the rock.